Twinkle R 3D appliance - An innovative functional skeletal class II corrector - Rohan Rai; Jacob Joseph; K Mithun; V Harshitha; Suhani Shetty (Wolters Kluwer Medknow Publications, 2020)
Functional appliances are widely used for regulating and directing growth in which commonly used are Frankel regulator and twinblock. Frankel regulator expands the orofacial arena for allowing growth by passive expansion, whereas twin block aids sagittal correction in retrusive mandible. Heres, an attempt to bring about both the changes in a single appliance where sagittal correction as well as keeping away constricted musculature is desired. In this appliance, passive and active expansion has been used simultaneously for better results. In the hindsight of the results, we could get in this case using Twinkle R 3D appliance, we hope that this appliance will be helpful in many more similar cases and act as adundum in clinician's armamentarium.